Factor Structure of the Adolescent Coping Orientation for Problem Experiences in Spanish Adolescents. Issue 3 (June 2013) - Forns, Maria; Kirchner, Teresa; Peró, Maribel; Pont, Elisenda; Abad, Judit; Soler, Laia; Paretilla, Claudia
The present study aimed to identify the best structure of the Adolescent Coping Orientation for Problem Experiences when applied to Spanish adolescents. A confirmatory factor analysis of five previous factor structures was conducted. As the data did not fit previous factor models, two exploratory factor analyses (first- and second-order) were carried out to identify the structure for Spanish adolescents and to analyse its criterion validity in relation to mental health, which was assessed by means of the Youth Self-Report. A first-wave sample of 1, 152 secondary education pupils (645 boys, 56%; 507 girls, 44%; M age = 14.4 yr., SD = 1.4) was involved in the confirmatory and exploratory factor analyses. A second-wave sample of = 374 secondary education pupils (188 boys, 50.5%; 186 girls, 49.5%; M age = 15.4 yr., SD = 1.1) was used to assess criterion validity. The results yielded eight first-order factors with Cronbach's α ranging from .63 to .79, and two second-order factors that replicated the Approach and Avoidance focus of coping. The paper discusses both the content of the extracted factors and mental health issues.